The Effect of the Minor’s Permission on Lifting Interdiction upon Him - Gherabi, Ahmed; Haibaoui, Abderrahmane (Journal of Legal Studies and Researches, 2022)
The interdiction of the minor’s money is considered a means of holding in order to protect it, but does the permission granted to a minor lift the confinement, even partially? What was deduced is that the actions of the authorized minor remain under the supervision of the legal representative and the judge. The research aims to clarify the reality of the permission on the minor and its effect on the interdict on him.